2001
DOI: 10.1177/14687984010012004
|View full text |Cite
|
Sign up to set email alerts
|

‘Many Differing Ladders, Many Ways to Climb...’: Literacy Events in the Bilingual Classroom, Homes, and Community of Three Puerto Rican Kindergartners

Abstract: In this article, we analyze aspects of the complex literacy lives of three Spanish dominant, mainland Puerto Rican kindergartners who were beginning readers at the time of the study. We investigate literacy as a social and cultural practice in the children's bilingual classroom, homes, and churches, describing the people who supported their developing literacy, their beliefs about literacy, and the characteristics of literacy events that the children coconstructed with them. Our analysis is based on data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…These young people participate in out-of-school literacy practices in various contexts. For example, research on the literacy practices of working-class Latino families in the United States has shown that children often engage in collaborative literacy activities in public spaces, such as the kitchen or the living room, which involve parents, siblings, cousins, and extended family members (e.g., Gonzalez et al, 2005;Volk & De Acosta, 2001). There are also cases where ethnic communities take a more active role in arranging out-of-school literacy practices for their children in order to pass on their cultural, religious, and linguistic heritages to their children.…”
Section: Out-of-school Literacy Practices In Multiple Languagesmentioning
confidence: 99%
“…These young people participate in out-of-school literacy practices in various contexts. For example, research on the literacy practices of working-class Latino families in the United States has shown that children often engage in collaborative literacy activities in public spaces, such as the kitchen or the living room, which involve parents, siblings, cousins, and extended family members (e.g., Gonzalez et al, 2005;Volk & De Acosta, 2001). There are also cases where ethnic communities take a more active role in arranging out-of-school literacy practices for their children in order to pass on their cultural, religious, and linguistic heritages to their children.…”
Section: Out-of-school Literacy Practices In Multiple Languagesmentioning
confidence: 99%
“…The focus of syncretism, therefore, is on transformation and not on fossilised forms (Gregory et al, 2004;Prinsloo, 2004). Although studies focusing particularly on syncretism have been collected under the heading of 'syncretic literacy studies' (Gregory et al, 2004), many are concerned with pre-literate talk and behaviour, since the children are of pre-school age (Volk, 1997(Volk, , 1999Volk & de Acosta, 2001;Drury, 2004). These studies show how young children, often with older siblings, syncretise home and school languages, narrative styles and literacy practices through play activities.…”
Section: Introductionmentioning
confidence: 98%
“…In particular, research related to home and community learning and mixed-age learning from around the world is cited (including Vygotsky 1978;Gregory 2001;Volk and De Acosta 2001;Rogoff 2003;Kenner 2005); studies of out-of-school learning are also referenced in this book, including Lee and Hawkins (2008) and Dash (2010). The study shows how, unlike in age-segregated mainstream school settings, children in complementary settings can learn and interact very effectively because they are in mixed-age groups, including not only students of various ages, but also parents and grandparents.…”
mentioning
confidence: 98%